Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.jctube.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Essential and toxic metals in serum of individuals with active pulmonary tuberculosis in an endemic region

Abstract: Trace elements play an important role in tuberculosis infection because their deficiencies can be associated with impaired immunity. Blood samples were collected from a total of 320 active pulmonary tuberculosis patients and healthy individuals. The serum concentrations of Zinc, Iron, Copper, Calcium, lead, Arsenic and Selenium were analyzed by atomic absorption spectrometry. The levels of trace elements were measured after 2, 4 and 6 months of anti-TB treatment initiation in TB infected groups. Compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
(56 reference statements)
2
7
0
1
Order By: Relevance
“…Low iron concentration is known in patients with TB and HIV 23,24. Low iron concentration in TB and TB-HIV-coinfected patients was reported in a previous study in the north-west of Ethiopia,25 and in Iran,26 which was similar to our finding. Iron has a significant role in the myeloperoxidase-dependent generation of hypochlorous acid which is a microbicidal factor 27.…”
Section: Discussionsupporting
confidence: 92%
“…Low iron concentration is known in patients with TB and HIV 23,24. Low iron concentration in TB and TB-HIV-coinfected patients was reported in a previous study in the north-west of Ethiopia,25 and in Iran,26 which was similar to our finding. Iron has a significant role in the myeloperoxidase-dependent generation of hypochlorous acid which is a microbicidal factor 27.…”
Section: Discussionsupporting
confidence: 92%
“…This regulation can occur at the transcriptional level, via DNA-binding metal-responsive transcriptional repressors which are responsible for the regulation of the transcription process as in many bacteria as M. tuberculosis. 4 From the results was found the means of zinc increased gradually during anti-tuberculosis and after therapy. The result was in agreement with a study of 6 who found that a lessened concentration level of serum Zn at the initial stage of treatment when compared to control, in men and in women (P < 0.05).…”
Section: Discussionmentioning
confidence: 95%
“…In spite of its biological and physiological assistances, its excessive level is toxic and might cause inhibition of M. tuberculosis growth. 4…”
Section: Introductionmentioning
confidence: 99%
“…Trace elements (Se, Cu, and Zn) Se levels were low in approximately 30% of patients, followed by Zn (* 25%) and Cu (3%). Lower levels of these metals have been observed in patients diagnosed with various infectious diseases (Skalny et al 2021;Weiss and Carver 2018;Oh et al 2019;Sepehri et al 2017). Se is an essential trace element in humans that supports antioxidant defense systems (Burk 2002) and, consequently, plays a role in immune-related diseases (Huang et al 2012;Hoffmann and Berry 2008).…”
Section: Discussionmentioning
confidence: 99%